Utilization of Blockchain-Based Smart Contracts in Banking: A Systematic Review of Technical, Regulatory, and Systemic Risk Dimensions - Fajar Gemilang Pradana; Taqiya Dipsatara (Jurnal Penelitian Sains Teknologi, 2026)
The advancement of blockchain technology has created significant opportunities for transforming the financial sector, particularly banking. One of the most transformative applications of this technology is the smart contract—self-executing digital agreements that automatically enforce predefined conditions without the need for intermediaries. This study presents a systematic literature review of 10 academic publications published between 2020 and 2025 to evaluate the utilization of smart contracts in the banking sector. The analysis focuses on three main dimensions: technical implementation, regulatory compliance, and systemic risk implications. The findings indicate that smart contracts have been implemented in automated lending systems, decentralized identity verification (KYC), asset tokenization, real-time auditing, and blockchain-based payment infrastructures. Despite these advantages, adoption remains constrained by security vulnerabilities in contract code, scalability limitations, interoperability challenges, and regulatory uncertainty across jurisdictions. This study also proposes a conceptual experimental framework for evaluating smart contract performance, security robustness, and compliance readiness within banking environments. The results contribute to a more integrated understanding of how smart contracts can be adopted safely and sustainably in highly regulated financial ecosystems.